Studi Kelayakan Taman Pendidikan Al – Qur’an Sebagai Sumber Belajar Pendidikan Nonformal - Andi Ahmad Gunadi; Zulfitria Zulfitria; Aswir Aswir (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2019)
Al Qur’an Learning Centres for Children (Taman Pendidikan Al-Qur’an) was supposed to be a complimentary nonformal education for both formal and informal education that many shared in society. This article was to analyze whether a feasibility study in terms of learning situation or education environment based on nonformal one. The research used a qualitative with descriptive design. The informants were derived from the managers Al Qur’an Learning Centres for Children , social figures and students’ parents. The results showed that Al Qur’an Learning Centres for Children as a informal education facility that complements formal and informal education was feasible to be maintained and developed to complete the religious-based on learning material both formal and informal education. In conclusion, learning situations or learning environments influence the feasibility as a learning resource for non-formal education. Keywords: Feasibility Study, Al Qur’an Learning Centres for Children, Nonformal Education